A Comparison of VLC Receivers That Incorporate Two Different SiPMs - Zubair Ahmed; Wajahat Ali; Grahame Faulkner; Steve Collins (IEEE Photonics Journal, 2023)
Previously, when selecting silicon photomultipliers (SiPMs) for use in visible light communications (VLC) systems the bandwidth of the SiPM has been a high priority. However, results of experiments on VLC receivers containing two different sizes of commercially available SiPMs show that, if equalization is used and the OOK bit time is less than one third of the duration of its output pulses, the SiPMs bandwidth doesn't significantly impact the receiver's performance. Consequently, for these data rates the criteria used to select which SiPM to incorporate in VLC receivers should put a higher priority on their area and photon detection efficiency than on their bandwidth. In addition, for these data rates, unless the SiPM becomes non-linear, the performance of a receiver containing a SiPM can be predicted based upon Poisson statistics.